Policy Formulation for Handling Stunting Using the Incremental Model in Padang Panjang City, West Sumatra Province - Sari, Defi Permata; Asrinaldi, Asrinaldi -; Valentina, Tengku Rika (Politicon : Jurnal Ilmu Politik, 2025)
Stunting has become a national issue, as evidenced by the issuance of Presidential Regulation No. 72 of 2021 concerning implementing the National Strategy for Accelerating the Reduction of Stunting. Although this national action plan has been developed, its implementation at the regional level requires effort. Even stakeholder coordination could have been more optimal, resulting in unmet objectives. This study highlights the importance of selecting an appropriate policy formulation model for addressing stunting, especially at the local level, considering the many stakeholders involved with diverse interests, particularly within government. Few researchers explain how the choice of policy model is made amidst the various alternative models available for government use. This research examines how the Padang Panjang City Government chose to address stunting using the incremental model. The incremental model is often viewed as non-progressive, tending toward the status quo, and reflective of conservative governance. However, the decision by the Padang Panjang City Government to use the incremental model has positively impacted the reduction of stunting prevalence. The key lies in how the Padang Panjang City Government maintains continuity and stability in the policies adopted by the central government, adapting and developing them according to the local community’s needs. This study demonstrates that the Padang Panjang City Government achieved continuity and stability in stunting management policies through an incremental approach shaped by four key variables: consensus and compromise, monitoring and evaluation, resource optimization, and resistance to radical changes. Using a qualitative case study method, data were gathered from interviews with key informants and document reviews. The findings emerged through a systematic process of coding and categorization, highlighting how incremental adjustments effectively reinforced policy sustainability over time.